Use of rainfall indices to analyze the effects of phosphate rocks on millet in the Sahel - Yamoah, C.F.; Bationo, B. André; Shapiro, Barry I.; Saidou, K (2011)
Two critical factors that explain low crop productivity in the Sahelian agro-ecozone are inadequate moisture and poor soils, particularly phosphorus (P) deficiency. The purpose of this long-term study was to explore the use of both local phosphate rock (PR) and inorganic P on yields and risk of millet returns under the uncertain rainfall regimes in the Sahel. Using the Standardized Precipitation Index (SPI) and Percent Confidence Limits (PCL) of the mean rainfall, the 10-year experimental period was grouped into rainfall classes. Results showed that the inorganic P fertilizers, that is, single superphosphate and triple superphosphate (SSP+N and TSP) gave the highest average yields. Also, millet yield increased with increasing P rates. However, typical farmers in the Sahel barely use P rates above 20 kg ha-1 in view of the high cost of imported fertilizers. A low application rate of the local PR, 10 kg P ha-1, increased millet yield between 44 and 67%. Stability analysis using yields from 15 farmers’ fields indicated that the traditional method of growing millet was the least stable (s.e. = 225) and had the lowest yield (314 kg ha-1). Generally, millet responded to P better when the preseason (May-June) were wet than dry, except where the non-acidulated PR (PRA) was applied every year (R2=0.99, P < 0.01) for both dry and wet preseasons. Risk analysis showed that acidulated PR regardless of rates gave the highest millet returns over variable cost of P fertilizer. The study recommends the promotion PR in order to guarantee stable yields and income for small farmers in the Sahel.